Instagram Post: Modifying the Use of Instagram to Increase Students’ Ability in Writing Cutline Caption - Sy, Yenny Ratnasarie; Sinaga, Tuntun (English Education: Jurnal Tadris Bahasa Inggris, 2023)
With the rapid advancements in technology, educators have increasingly explored the utilization of social media platforms as educational tools. Among these platforms, Instagram has emerged as a prominent choice due to its widespread popularity. This transformation has seen Instagram being repurposed from a mere entertainment tool to an educational medium, particularly in the domain of language instruction. English teachers, in particular, have embraced this platform to facilitate the teaching of essential language skills such as speaking and writing. This study aims to investigate the effectiveness of using Instagram in enhancing students' proficiency in writing cutline captions. The research subjects consisted of 32 twelfth-grade students from SMAN 1 Jatiagung, South Lampung, Lampung Province. Data collection was carried out through a pretest and posttest writing assessment, and the obtained data were subjected to descriptive quantitative analysis. The findings revealed a notable improvement in students' ability to write cutline captions following the integration of Instagram into the instructional process. These results highlight the potential of Instagram as a valuable tool for fostering students' writing skills, specifically in the context of crafting engaging and concise captions. The implications of this study contribute to the expanding body of literature on technology-mediated language learning and underscore the importance of incorporating social media platforms into educational settings for effective language instruction